Analisis Dampak Kebijakan Perubahan Publik Harga BBM terhadap Perekonomian Rakyat Indonesia - Chintia Simbolon, Irma; Karolina Sidebang, Lusyana; Theofani Margaret, Natasia; Valencia Pangaribuan, Sheryl; Kemala Dewi Lubi, Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out the government's role in society regarding rising fuel prices, and also aims to find out what causes the increase in fuel prices. This research uses a qualitative research methodology and uses a descriptive approach where the researcher will compile a complex picture and analyze it word by word. The research results reveal that rising oil prices can have a significant impact on society and the country's economy. The research results also show that the fuel price change policy has a significant impact on the inflation rate, with direct consequences for people's purchasing power. In addition, certain economic sectors such as transportation and manufacturing are also significantly affected. This analysis provides insight into how fuel price policy can be an important instrument in managing economic stability and social welfare in Indonesia. The policy implications resulting from this research can provide guidance for more effective and sustainable policy planning in the context of changes in fuel prices in the future.